SLC34A3 Intronic Deletion in an Iranian Kindred with Hereditary Hypophosphatemic Rickets with Hypercalciuria - Hasani-Ranjbar, Shirin; Ejtahed, Hanieh-Sadat; Amoli, Mahsa M.; Bitarafan, Fatemeh; Qorbani, Mostafa; Soltani, Akbar; Yarjoo, Bahareh (Journal of clinical research in pediatric endocrinology, 2018)
To describe clinical findings, biochemical profile and genetic analysis in an Iranian kindred with hereditary hypophosphatemic rickets with hypercalciuria (HHRH). Clinical examination and biochemical profile results and gene analysis of 12 members of a family of a patient previously diagnosed with HHRH due to mutation. Ten healthy controls were also evaluated. Of the twelve family members three were homozygote and seven heterozygote for the same variant found in the proband while two others were unaffected. All patients had significantly increased risk of kidney stone formation, bone deformities and short stature compared with unrelated healthy controls. The heterozygous patients displayed milder clinical symptoms compared with homozygous patients. In particular they had mild or no hypophosphatemia and they did not develop skeletal deformities. Recurrent renal stones and hypercalciuria were the main presentations of the heterozygous patients which may be confused with familial hypercalciuria. In addition, biochemical analysis showed significantly low serum sodium and elevated alkaline phosphatase levels in these patients. Genetic counseling and screening for mutations can be helpful in adult onset phenotype with unexplained osteoporosis, bone deformities and especial recurrent renal stones. In subjects with vitamin D deficiency the results should be interpreted cautiously.